Organoleptic Properties of Salted Chicken Eggs was added Spices - Marfu'ah, Nuun; Sugiarto, Sugiarto (FAPETKAN UNTAD, 2019)
This addition of herbs and spices in the salted eggs is one of the ways for extending shelf life of salted eggs and to add flavor in the salted eggs, apart from the salty taste because there is the addition of salt. Herbs and spices like garlic, red onion and pepper are natural seasoning flavor that contains lot of active chemical substances that are beneficial to the body apart from giving more popular flavor with consumer. The aim of this research is to find out organoleptic properties of salted chicken eggs that are added by herbs and spices. Variance analysis results showing that salted eggs with the addition of herbs and spices from various treatment have no real effect on organleptic properties of salted eggs : egg yolk color, salty taste of egg whites and egg yolk nervousness. This matter probably caused because when salted egg are soaked with herbs and spices, salted eggs products produced change color into darker color, same saltiness and egg yolk nervousness from chicken is different from the salted egg that derives from ducks. Conclusion of this research is salted chicken eggs with the addition of herbs and spices is more preferable by panelist because it tastes more savory even though it dont have significant egg yolk color, salty taste of egg whites, and egg yolk nervousness.Keyword: organoleptic, salt eggs,herbs and spices.